Studies on the reactions of [AuCl4]− with different nucleophiles in aqueous solution - Puchta, Ralph; Bugarčić, živadin D.; et al. (Dalton Transactions, 2014)
In order to distinguish between the different types of reactions that can occur between Au(iii) species and simple nucleophiles, including iodide, bromide, nitrite, thiourea, pyridine and dimethyl sulfoxide, spectrophotometric techniques including stopped-flow and rapid-scan measurements were employed under specific reaction conditions. All experiments were performed in a 0.4 M NaCl aqueous solution to maintain a high chloride concentration and a constant ionic strength. The temperature dependence of the observed rate constants confirmed the associative nature of the ligand substitution reactions. The redox behaviour of the Au(iii) species was studied by cyclic voltammetry and confirmed the reversible redox transitions at ca. 0.38 V (SCE, E = 0.1 V s−1). Results obtained during the reaction progress were attributed to the formation of Au0. This oxidation state was observed for the reactions with thiourea, iodide and nitrite, whereas pyridine showed a potential shift only to Au(i) formation, while bromide showed potential shifts typical of ligand substitution reactions. The reaction with dimethyl sulfoxide was studied using1H NMR and ab initio (RMP2(full)/LANL2DZp) techniques, which revealed why Au(iii) does not react with sulfoxide. The results are discussed in terms of the importance of the stability of the Au(iii) species in aqueous solutions of the selected salts and bases. In this way, one could differentiate between a possible three-electron inner-sphere redox process and/or a substitution process during the rapid initial step of the reactions. © 2014 The Partner Organisations.
CRIS-Team Scopus Importer:2026-01-22